School Library Training Using Slims 9 Bulian: Pelatihan Perpustakaan Sekolah Menggunakan Slims 9 Bulian - Erni Rouza; Satria Riki Mustafa; Aditya Hermawan (Institut Riset dan Publikasi Indonesia, 2023)
The website-based school library is a system that allows students, teachers and school staff to access a collection of books available in the library via the internet. SlimS (Senayan Library Management System) is a software open source used to manage school-based libraries website. Withuse SliMS 9 Bulian, schools can increase their efficiency and productivity as well as provide convenience for their users in accessing the available book collections. In addition, SliMS can also facilitate the management and monitoring of library activities, so that it can assist in improving service quality. The output that will be produced after implementing the SliMS Bulian application is to provide knowledge about SliMS 9 Bulian one of the software library manager, what features it has, its advantages and being able to optimize utilization software to all members of the Muhammadiyah Rambah Hilir Middle School and at the same time provide knowledge about the use of information technology, especially in library management.